EFISIENSI PAKAN DAN JUMLAH BAKTERI ASAM LAKTAT USUS AYAM BROILER YANG DIBERI CAIRAN SAUERKRAUT DALAM AIR MINUM - H.Nur Fauziyah Hasanah; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
This study aims to prove the sauerkraut liquids in the drinking water of broiler chickens to weight gain, final weight, feed consumption, feed efficiency and the amount of lactic acid bacteria intestine of broilers. A total of 24 chickens broiler DOC with an average weight of 25-35 gr/tail. Broiler chickens were randomly divided into 4 groups.. Each group was given liquids sauerkraut 0 ml/L, 0.5 ml/L, 1.0 ml/L, and 1.5 ml/L in drinking water for 35 days. The results showed the treatment liquids concentration sauerkraut 1,5 ml/L in drinking water have a significant effect (P <0,05) on body weight gain, final weight, feed intake, feed efficiency and the amount of lactic acid bacteria intestines of broiler chickens. Average of body weight gain of broilers given liquids sauerkraut 1.5 ml/L in drinking water significantly (P <0.05) higher than the weight gain of broilers concentration 0 ml/L. Average of final weight of broilers given liquids sauerkraut 1,5 ml/L in drinking water significantly (P <0.05) higher than the final weight of broilers concentration 0 ml/L. Average of consumption of broiler chicken feed given liquids sauerkraut 1,5 ml/L significantly (P <0.05) lower than the consumption of broiler chicken feed concentration of 0 ml/L. Average of FCR of broilers given liquids sauerkraut 1,5 ml/L significantly (P <0.05) lower than the FCR of broilers concentration of 0 ml/L. The average amount of lactic acid bacteria intestines of broilers given liquids sauerkraut 1.5 ml/L significantly (P <0.05) higher than the amount of lactic acid bacteria intestines of broilers concentration of 0 ml/L. On the research that use of liquids sauerkraut in drinking water 1,5 ml/L can improve feed efficiency and amount of lactic acid bacteria broiler chicken intestines of 23.5%, and 19.4%. Keywords: Broiler chickens, sauerkraut, feed efficiency, the amount of lactic acid bacteria